VARIASI STIMULUS DALAM PELATIHAN KEWIRAUSAHAAN STIMULUS VARIATION IN ENTREPRENEURSHIP TRAINING - Sarippudin Sarippudin (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
Entrepreneurship training aims to prepare participants for entrepreneurship. This training is important because entrepreneurship is not an easy case. Training becomes a way to inculcate the entrepreneurial mentality to be determined to start a business, to face some risks and to be tenacious. In order to create this training succeed, instructors as training spearheads must have skills in conveying materials, even inspiring the participants. The stimulus variation is a form of instructors’ skill. Stimulus variation makes the learning process works well the training becomes fun, so that participants can be comfortable and voluntarily follow the learning process. Training is not a monotonous activity. The instructor can be an inspiration in the classroom, no longer just as a transmitter of learning materials.